Akkadian kaṣāru and Semantic Equivalents - Waldman, Nahum M.
I. to wear, wrap, tie on: II. weave, plait, create, build; III. assemble, gather, organize, kiṣru = band, army; IV. congeal, thicken, solidify; V. weave, plan, plot.